PENILAIAN STATUS DOMAIN SUMBER DAYA IKAN LEMURU DENGAN PENDEKATAN EKOSISTEM YANG DIDARATKAN DI PPI KEDONGANAN, BALI - Ketut Tika Suariningsih; I Wayan Restu; Made Ayu Pratiwi (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2021)
PPI Kedonganan is a fish landing base located in Kedonganan Village, Kuta District, Badung Regency. One of the fish commodities that landed at PPI Kedonganan is Lemuru Fish (Sardinella lemuru). The high rate of catching Lemuru must be balanced with proper management so that Lemuru Fish Resources remain sustainable. This study was conducted to determine the status of the utilization of Lemuru fish resources. The study was conducted from January 2021 to March 2021. Data collection was carried out by observation and interviews. Data analysis of each indicator was carried out using a multi-criteria analysis approach with composite index assessment and visualization by flag model. Indicators were observed the trends of fish size, the proportion of juvenile fish were caught, the species composition, range collapse of fish resources, Endangered, Threatened, and Protected species. The status assessment of the Lemuru resource domain which landed at PPI Kedonganan is in the good category with a composite value of 66.7. Results of the trend indicators of fish size is relatively fixed, the proportion of fish juvenile caught about 90%, the composition of species caught was 100% of the target fish i.e, lemuru that caught by using gill net, range collapse of fish resources as much as 57% of fishermen expressed relatively fixed in looking for fishing grounds, and ETP species not found. Keywords: EAFM; Lemuru Fish; Fisheries Management; PPI Kedonganan.